Transformational Leadership and Dynamic Managerial Capabilities in Public Sector Innovation (Jurnal Bina Praja, 2024)
The study examines the role of transformational leadership and Dynamic Managerial Capabilities in public sector innovation, specifically in addressing the challenges of managing the livelihood eligibility of the community, including older people, in order to build an elderly-friendly community. The study focuses on the leadership of Jambi Mayor and Vice Major in employing innovation to realize Jambi as a Smart Living. This descriptive qualitative study aims to identify new information related to the transformational leadership and Dynamic Managerial Capabilities of the Jambi Government in innovating feasible urban living. The authors identified transformational leadership as a major style in carrying out innovation and dynamic managerial capabilities. The study found that Jambi City is continuously promoting the importance of creating smart living as one of the smart city indicators, especially in elderly-friendly cities, through the leadership of its mayor and vice mayor. Both initiated change by identifying challenges and opportunities, finding good examples of smart living, inspiring and implementing innovations, encouraging changes in how the bureaucracy works, and motivating civil servants to improve their attitudes and assumptions, especially toward health services for the elderly. The study concludes that leadership style and dynamic managerial ability to adapt to change contribute to the success of smart living innovation.
Keywords: Transformational Leadership; Smart City; Elderly-Friendly